Prenatal diagnosis and outcome of fetuses with isolated agenesis of septum pellucidum: cohort study and meta‐analysis. (18th January 2022) - Pasquo, E. DI; Kuleva, M.; Arthuis, C.; Morganelli, G.; Ormitti, F.; Millischer, A.‐E.; Grevent, D.; Ville, Y.; Ghi, T.; Salomon, L. J.
ABSTRACT: Objective: To evaluate the postnatal outcome of children with a prenatal diagnosis of apparently isolated agenesis of the septum pellucidum (ASP). Methods: A retrospective cohort study of cases of prenatally diagnosed ASP followed in two tertiary centers and a meta‐analysis combining data from the cohort study with data from published studies identified in a systematic review were carried out. Only cases with apparently isolated ASP on antenatal ultrasound and/or magnetic resonance imaging and with available postnatal follow‐up data were considered eligible for inclusion. The following outcomes were analyzed: incidence of chromosomal anomalies, agreement between antenatal and postnatal findings, overall incidence of septo‐optic dysplasia (SOD) and incidence of major neurological disability (motor, language, coordination or behavioral disorder or epilepsy) in non‐SOD children. The incidence of SOD in infants with apparently normal optic pathways on antenatal imaging was also evaluated. Results: Fifteen cases of isolated ASP, with median postnatal follow‐up of 36 months (range, 12–60 months), were selected from the two centers. Six previously published studies met the inclusion criteria for the systematic review and a total of 78 cases were eligible for the analysis, including the 15 cases from our series. Genetic tests were carried out antenatally in 30 fetuses, of which two had an abnormal result (pooled proportion, 9.0% (95% CI, 1.8–20.7%); I 2 = 0%). Additional or discordant imaging findings were noted postnatally in 9/70 (pooled proportion, 13.7% (95% CI, 3.5–29.0%); I 2 = 63.9%) cases. Of all 78 neonates with available follow‐up, SOD was diagnosed postnatally in 14 (pooled proportion, 19.4% (95% CI, 8.6–33.2%); I 2 = 51.2%). In 60 cases, the optic pathways were considered to be normal on antenatal imaging, and six of these (pooled proportion, 9.1% (95% CI, 1.1–24.0%); I 2 = 62.0%) were diagnosed postnatally with SOD. Of the 46 infants with available neurological follow‐up who were not affected by SOD, a major neurological disability was diagnosed in three (pooled proportion, 6.5% (95% CI, 0.5–18.6%); I 2 = 40.1%). Conclusions: In the vast majority of cases with a prenatal diagnosis of apparently isolated ASP, the prognosis is favorable. However, an additional anomaly is detected after birth in about 14% of cases and has a negative impact on clinical outcome. Detailed antenatal assessment of the brain and optic pathways is strongly recommended in order to identify the presence of associated anomalies. Antenatal visualization of apparently normal optic pathways does not rule out SOD. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.